The maximal runaway temperature of Earth-like planets - Shaviv, Nir; Shaviv, Giora; Wehrse, Rainer (Icarus, 2011)
In Simpson’s (Simpson, G.C. [1927]. Mem. R. Meteorol. Soc. II (16), 69-95) classical derivation of the temperature of the Earth in the semi-gray model, the surface temperature diverges as the fourth root of the thermal radiation’s optical depth. No resolution to this apparent paradox was yet obtained under the strict semi-gray approximation. Using this approximation and a simplified approach, we study the saturation of the runaway greenhouse effect. First we generalize the problem of the semi-gray model to cases in which a non-negligible fraction of the stellar radiation falls on the long-wavelength range, and/or that the planetary long-wavelength emission penetrates into the transparent short wavelength domain of the absorption. Second, applying the most general assumptions and independently of any particular properties of an absorber, we show that the greenhouse effect saturates and that any Earth-like planet has a maximal temperature which depends on the type of and distance to its main-sequence star, its albedo and the primary atmospheric components which determine the cutoff frequency below which the atmosphere is optically thick. For example, a hypothetical convection-less planet similar to Venus, that is optically thin in the visible, could have at most a surface temperature of 1200-1300K irrespective of the nature of the greenhouse gas. We show that two primary mechanisms are responsible for the saturation of the runaway greenhouse effect, depending on the value of λcut, the wavelength above which the atmosphere becomes optically thick. Unless λcut is small and resides in the optical region, saturation is achieved by radiating the thermal flux of the planet through the short wavelength tail of the thermal distribution. This has an interesting observational implication, the radiation from such a planet should be skewed towards the NIR. Otherwise, saturation takes place by radiating through windows in the FIR.